1982
DOI: 10.1051/rnd:19820607
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the stage of the oestrous cycle on the follicular population in pony mares

Abstract: Summary. In the middle of the breeding season, 16 pony mares (n = 4 per day) were slaughtered on four different days (days 6, 14, 17 and the preovulatory day) of the oestrous cycle, day 0 being the day of the last ovulation. All the ovaries were examined histologically ; the number, size and atresia (defined by granulosa cell pyknosis) of all follicles larger than 1 mm in diameter were studied, using a Kryotome-video recorder-TV system.Follicular distribution of all the sizes studied (1-5 mm, 5-10 mm, > 10 mm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
(9 reference statements)
3
5
0
Order By: Relevance
“…As noted earlier, this is also consistent with the experimental evidence that follicles, of a size that can be counted non-invasively, likely do not contribute significantly to circulating AMH concentrations (Sahambi et al 2008, Claes et al 2016. Follicles of smaller diameter are more numerous (Driancourt et al 1982a) and therefore contribute most to AFC. Even though losing their ability to secrete AMH, this probably explains the positive correlation between antral follicle count and circulating AMH in published studies that employed larger numbers of mares and more frequently determined AFC (Claes et al 2015).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As noted earlier, this is also consistent with the experimental evidence that follicles, of a size that can be counted non-invasively, likely do not contribute significantly to circulating AMH concentrations (Sahambi et al 2008, Claes et al 2016. Follicles of smaller diameter are more numerous (Driancourt et al 1982a) and therefore contribute most to AFC. Even though losing their ability to secrete AMH, this probably explains the positive correlation between antral follicle count and circulating AMH in published studies that employed larger numbers of mares and more frequently determined AFC (Claes et al 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Hemi-ovariectomy was performed at random with respect to cycle stage which was verified by gross examination of ovaries and progesterone concentrations in peripheral blood (Munro & Stabenfeldt 1984) (data not shown). Based on previous studies in pony mares, follicle distribution is equal between left and right ovaries (Driancourt et al 1982a). An incision was made over the lumbar fossa and muscle tissues separated bluntly to gain access to the peritoneal cavity.…”
Section: Experiments 2: Effects Of Hemi-ovariectomy On Amh Concentratimentioning
confidence: 95%
“…An earlier study [34] reported that equine follicle population varies from 5600 to 75,000, which is considered low when compared with other domestic species (i.e., swine: 185,000-779,000 [35]; bovine 10,043-253,000 [36]). The low number and density of preantral follicles in the equine species might be because of the potential heterogeneous distribution of these structures within the ovary [11] regulated by genes and factors that control survival, proliferation, colonization, and inclusion of primordial germ cells in follicular structures [37].…”
Section: Discussionmentioning
confidence: 97%
“…Smeaton and Robertson (1971) and Bherer, Matton and Dufour (1977) suggested that three waves of follicles develop during the ewe cycle : on days 6 to 9 and 13 to 15 large follicles were marked which did not ovulate, after day 15 they did ; (3) the demonstration of peaks in oestradiol-170 secretion on days 3 and 4 (Cox, Mattner and Thorburn, 1971), 6 to 9 and 11 to 15 (Mattner and Braden, 1972 (Brand and De Jong, 1973), suggests that preovulatory enlargement can occur under a wide range of hormonal levels and pulse frequencies. This high degree of follicular activity during the luteal phase is a common feature in sheep, cows (Rajakoski, 1960) and saddle-type mares (Driancourt, Palmer and Bour, 1983), but is seldom found in women (Gougeon, 1981) or pony mares (Driancourt, Mariana and Palmer, 1982).…”
Section: Introductionmentioning
confidence: 99%